On Some Differential Properties of Small Small Sobolev-Morrey Spaces - Najafov, Alik Malik oglu (Eurasian Mathematical Journal, 2021)
In the paper small small Sobolev-Morrey spaces are constructed. Differential and differential-difference properties of functions belonging to the constructed space are studied by the integral representation method.